A importância do profissional "Capelão": força vital na consolidação do Exército Brasileiro - Crivelari, Ubiratan Nelson (2009)
This work aims to investigate the military chaplain s work in the Brazilian Army. This ministry has been seen since the Portuguese arrival to Brazil and as the time pass it ripens and became a well developed structure. It is obvious that it has a conspicuous work in the men s hands who have the interest in giving spiritual and emotional support to the militaries as well as to their families. The religious work has a vital importance in military life since the soldier will have the chance to have a more balanced life. We can also realize through this work that besides the job carried out by the Catholic Roman Church, a great job has been done by the Evangelical chaplains. According to the statistics, the number of evangelical soldiers has been growing in an outstanding way. This research is based on parts of interviews with two Brazilian Army chaplains, a priest and a pastor who will mention the gigantic work done in this Army. The chaplain is vital in the consolidation of Brazilian Army.